The Influence of Work Facilities, Job Placement and Work Ability on Employee Performance Central Sulawesi Provincial Youth and Sports Office - Ulfa; Rajindra; Rukhayati (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the influence of work facilities, job placement, and employability on employee performance at the Central Sulawesi Provincial Youth and Sports Office. The method used is a quantitative approach with multiple linear regression analysis to determine the relationship between independent variables and dependent variables. Data was collected through the distribution of questionnaires to respondents who were active employees in the agency. The results showed that partially or simultaneously, the three independent variables—work facilities, work placement, and work ability—had a significant effect on employee performance. Adequate work facilities provide comfort and support the effectiveness of the task. The right job placement can increase motivation and productivity, while high work ability reflects individual competence in completing tasks well. These findings indicate the importance of managerial strategies that focus on the provision of facilities, competency-based placement, and employee capacity building in an effort to improve organizational performance. This study recommends that the Youth and Sports Office continuously develop an integrated human resource management system to support the optimization of employee performance.